XPS and GDOES Characterization of Porous Coating Enriched with Copper and Calcium Obtained on Tantalum via Plasma Electrolytic Oxidation - Krzysztof Rokosz; Tadeusz Hryniewicz; Patrick Chapon; Steinar Raaen; Hugo Ricardo Zschommler Sandim (Journal of Spectroscopy)
XPS and GDOES characterizations of porous coatings on tantalum after Plasma Electrolytic Oxidation (PEO) at 450 V for 3 minutes in electrolyte containing concentrated (85%) phosphoric acid with calcium nitrate and copper (II) nitrate are described. Based on the obtained data, it may be concluded that the PEO coating consists of tantalum (Ta5+), calcium (Ca2+), copper (Cu2+  and Cu+), and phosphates (PO43-). It has to be pointed out that copper and calcium are distributed throughout the volume. The authors also propose a new model of PEO, based on the derivative of GDOES signals with sputtering time.